My Children First: Conflicting Choices about Education For Mothers who Receive Welfare - Mary Ziegler (Adult Education Research Conference, 2004)
Participation continues to perplex those who provide adult education. This study explored the reasons women who receive welfare chose not to participate in adult education programs designed for them. Countervailing forces of poverty and participants’ aspirations of a better life for their children interacted with personal, relational, and institutional factors.